The role of oxidative stress in antipsychotics induced ovarian toxicity - Elmorsy, Ekramy; Al-Ghafari, Ayat; Aggour, Amal Misbah; Khan, Raheela; Amer, Saad A. (Elsevier, 2017)
This study tested the hypothesis that oxidative stress could be an underlying mechanism for APs-induced ovarian cytotoxicity and reproductive dysfunction. Rat ovarian theca interstitial cells (TICs) were isolated and treated with four APs [chlorpromazine (CPZ), haloperidol (HAL), risperidone (RIS) and clozapine (CLZ)]. MTT assay was used to test the effects of these antipsychotics on TICs viability and to estimate their 50% inhibitory concentrations (IC50s). The effects of APs (IC50s and 1 μM concentrations) on the activities of caspases-3, -8 and -9, reactive oxygen species (ROS) production, total intracellular glutathione and lipid peroxidation (LPO) in TICs were assessed. The effect of antioxidants (reduced glutathione (GSH) and quercetin) on the APs-induced cytotoxicity on TICs was investigated. MTT assay showed all APs to reduce TICs viability. CPZ, HAL and CLZ significantly increased the activity of caspases-3, -8 and -9 (P < 0.0001, < 0.0001 and < 0.01, respectively). All APs at IC50s significantly (P < 0.0001) increased ROS production, decreased total intracellular glutathione and increased LPO. MTT assay in the presence of antioxidants (reduced GSH (5 mM) or quercetin (50 mM)) showed each antioxidant to significantly inhibit the effects of APs at their IC50s on TICs viability. In conclusion, oxidative stress seems to be a possible mechanism for APs-induced ovarian and reproductive toxicity.